Modelling, Sensitivity and Exergy Analysis of Triple-Pressure Heat Recovery Steam Generator - F. Zehra Özçelik; Suha Orçun Mert; Ceyda Kök (MANAS: Journal of Engineering)
Combined with the increasing demand for environmental pollution and electrical energy, combined cycle power plant power plants are increasingly important. It is necessary to increase the performance of power plants, reduce carbon emissions and increase energy production. Any change to the heat recovery steam generator design is an important component of the combined cycle power plant, as it directly affects the performance of the combined cycle power plant. This study describes the modeling, sensitivity and exergy analysis of a HRSG in a combined cycle power plant. Three-pressure HRSG was modeled with the Aspen Plus simulation program and sensitivity analysis was performed. At the same time, energy and exergy analyzes were made for each component in the combined cycle power plant.